Early life nicotine exposure alters mRNA and microRNA expressions related to thyroid function and lipid metabolism in liver and BAT of adult wistar rats. (1st March 2021) - Peixoto, Thamara Cherem; Gaspar de Moura, Egberto; Quitete, Fernanda Torres; Simino, Laís Angélica; Torsoni, Adriana Souza; Torsoni, Marcio Alberto; Manhaes, Alex Christian; Lisboa, Patricia Cristina
Abstract: In rats, maternal nicotine exposure during lactation induces obesity, thyroid dysfunction, brown adipose tissue (BAT) hypofunction and liver alterations in adult offspring. Both thyroid function and lipid metabolism are influenced by gene silencing mediated by microRNAs (miRNAs). Here we investigated long-term effects of early nicotine exposure on molecular and epigenetic mechanisms closely related to thyroid and lipid metabolism, through the expression of mRNAs and miRNAs in BAT and liver of adult male and female offspring. At postnatal day 2 (PND2), lactating control (CON) or nicotine (NIC) dams were subcutaneously implanted with osmotic minipumps containing, respectively, saline or 6 mg/kg nicotine. Litters were adjusted to 3 males and 3 females. Offspring's euthanasia occurred at PND180. In the BAT, NIC females showed higher Dio2 mRNA expression, while miR-382* expression was not altered in both sexes. In the liver, NIC offspring of both sexes showed lower Dio1 mRNA expression and higher miR-224 expression, while only NIC females had higher miR-383 and miR-21 expressions. NIC offspring of both sexes showed higher mRNA expression of SCD1 in the liver; NIC males had decreased CPT1 expression, whereas NIC females had increased FASN, miR-370 and miR-122 expressions. Regardless of sex, alterations in liver Dio1, miR-224 and SCD1 expressions are involved in the disturbances caused by maternal nicotine exposure during breastfeeding. Interestingly, females had more altered miRs in the liver. Early nicotine exposure induces a sex dimorphism, particularly regarding hepatic lipid metabolism, through miRs expression. Highlights: Early nicotine exposure alters microRNAs in adult offspring. Nicotine exposure during lactation induces a sex dimorphism in hepatic miRs expression. Changes in Dio1 and miR-224 can be involved in thyroid dysfunction in both sexes.